Cyberbullying : How To Stay Safe on Social Media? - Mohd Haris, Ahmad Firdaus (International Journal of Human and Health Sciences (IJHHS), 2023)
Facebook, TikTok, Instagram, Twitter. There is rarely anyone without any of these social media accounts. According to 2020 Internet User Survey by Malaysian Communications and Multimedia Commission (MCMC), 88.7% of Malaysians are internet users. Out of that number, 93.3% of users use social media extensively. Social media has enabled users to connect with family and friends. It has done wonders to small businesses to prosper. It has also empowered communities to grow and prosper. However, there is one dark side to it; CYBERBULLYNG. According to the Merriam Webster dictionary, bullying is defined as “abuse and mistreatment of someone vulnerable by someone stronger, more powerful”. Most of the time, bullying is done when a bully is in the presence of his or her victim. However, in the cyber world, bullying extends beyond the physical presence. The act of bullying can be done 24 hours a day, by anyone at any time. A victim can be harassed with harsh comments via any social media accounts and even through text messages which sometimes invade the victim’s own privacy. There is no clear guidelines and policy regarding cyberbullying. Any form of enforcement is lax due to the nature of the internet being free for all. Thus, it is imperative to empower oneself to understand how to use social media effectively to prevent from being cyberbullied and also NOT to be a cyberbully. There are also tools that can be used in each social media platform to report such cyberbullying issues and also to report to the relevant agencies such as the Royal Malaysian Police and Malaysian Communications and Multimedia Commission. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S14